Uji Potensi Fraksi n-Heksan Daun Keji Besi (Hemigraphis repanda L.) Sebagai Antibakteri Terhadap Escherichia Coli dan Bacillus Cereus Beserta Penentuan Konsentrasi Hambat Minimum (KHM) - Alfina Nurrahman; Rahmat Hidayat; Annora Rizky Amalia (Journal of Health, Medical, and Psychological Studies, 2025)
This study aimed to evaluate the antibacterial potential of the n-hexane fraction of Keji Besi leaves (Hemigraphis repanda L.) against Escherichia coli and Bacillus cereus, as well as to determine its Minimum Inhibitory Concentration (MIC). Keji Besi leaves were extracted by maceration using 96% ethanol, followed by liquid–liquid fractionation with n-hexane. The antibacterial activity was assessed using the disc diffusion method, while MIC values were determined using the broth dilution method. Phytochemical screening revealed that the n-hexane fraction predominantly contained steroid and triterpenoid compounds. The disc diffusion assay showed that the n-hexane fraction exhibited stronger inhibitory activity against B. cereus than E. coli, with the largest inhibition zone observed at an 80% concentration. MIC determination indicated that the MIC value for B. cereus was 40% (w/v), whereas E. coli required a higher concentration of 80% (w/v) to inhibit bacterial growth. These findings suggest that the n-hexane fraction of Keji Besi leaves demonstrates selective antibacterial activity, particularly against Gram-positive bacteria. Therefore, this fraction has promising potential to be developed as a natural antibacterial agent, especially for infections caused by Gram-positive pathogens.